(untitled) (International Journal of Studies in Nursing, 2020)
Exclusive breastfeeding (EBF) plays a pivotal role in determining the optimal health and development of infants with reduction in infant mortality. This study focuses on those factors which place nursing mothers in the likelihood of not adopting and practicing EBF. It is a descriptive study that utilized a multi-stage sampling technique. A structured questionnaire, mean and standard deviation were used. The result shows that the EBF practice among nursing mothers is high with a grand mean and standard deviation of 2.75 (0.61). Those with secondary qualification and below had 3.10(0.37) while tertiary had 2.23 (0.41). Mothers aged 25 and below had